Non-surgical endodontic management of extensive periapical lesion with combination of calcium hydroxide and bioceramic dressing: A case report - Hajwan, Ismawan; Rachmudin, Afniati (Hasanuddin University, 2025)
Introduction:Endodontic management of extensive periapical lesions requires special consideration to achieve optimal clinical outcome. Calcium hydroxide dressing has been widely used in root canal treatment. In some cases of extensive periapical lesions, the use of other materials may be considered. When Calcium hydroxide combined with bioceramic dressings, the effectiveness of endodontic treatment can be improved.Case Report:A 21-year-old female came to RSGM Hasanuddin University with complaints of left maxillary front tooth pain accompanied by palatal swelling since 4 days ago. Intra oral examination of tooth 22 revealed composite filling, vitality test (-), percussion test (+), palpation test (+). Periapical radiographic examination showed radiolucency in the middle third of the root to the apical third with size 10.74 mm x 14.92 mm. Diagnosis was pulp necrosis with acute apical abscess. Differential diagnosis was periapical cyst. The treatment plan was multi-visit root canal treatment with a combination of calcium hydroxide and bioceramic as root canal medicament and obturation using thermoplastic obturation technique with bioceramic sealer. Radiographic findings showed that the periapical lesions were healed following therapy.Discussion:The combination of calcium hydroxide and bioceramic materials in root canal treatment of extensive periapical lesion offers the better disinfection, enhanced tissue healing. Calcium hydroxide provides antimicrobial properties and promotes healing, while bioceramic materials offer bioactivity and biocompatibility.Conclusion:The combined use of calcium hydroxide and bioceramic as dressings in root canal treatment of teeth with extensive periapical lesions showed significant results with enhanced healing of periapical lesions.